Conceptualizing Muslim Consumer Ethical Behaviour and its Antecedents - Muhammad Iskandar Hamzah; Abdul Kadir Othman; Faridah Hassan; Jalilah Ahmad; Muhammad Abdul Adib Abdul Aziz (International Journal of Supply Chain Management, 2018)
Businesses are gradually realizing the importance of corporate social responsibility in securing greater returns in their operations. This approach is intended to create good image for the company subsequently to attract consumers to purchase products or services from that company. The issue now is whether the consumers are ethical or not in their decision to purchase products or services from the company. Ethical consumers will think twice before making their decision to purchase. Within the western world, pertinent issues like human rights, environmental concern, sustainability, intellectual property rights and others are recognized as the major concern for the consumers before making purchase decision. In other parts of the world especially in developing countries, Muslim community is a steadily growing consumer group that should not be rightfully ignored. Studies in the areas of Muslim consumer ethics and purchasing behaviour have still remained relatively unexplored, thus, calling for this research to lessen the gap. The objective of this study is to conceptualize, develop and validate a Muslim consumer ethical model. The expected result of the study is the development of the Muslim consumer ethical model that can be used to identify the determinants of this behaviour. The results will provide deep insights on the right strategies that could be devised by companies based on the model.